Waveguide integration of a >4.7‐THz quantum‐cascade laser. Issue 2 (14th January 2023) - Nuttall, Eleanor; Han, Yingjun; Pardo, Diego; Kondawar, Sanchit S.; Brewster, Nick; Salih, Mohammed; Li, Lianhe; Horbury, Michael D.; Davies, A. Giles; Linfield, Edmund H.; Wang, Hui; Dean, Paul; et al.
Abstract: Waveguide integration of terahertz quantum cascade lasers (THz QCLs) is demonstrated at frequencies above 4.7 THz. A precision micromachining technique, followed by diamond‐turning and electroless‐plating has been used to manufacture hollow rectangular waveguides with integrated diagonal feedhorns. It is shown that surface roughness at the ≈ 1 μ m ≈ 1 μ m level is achieved, enabling outcoupling of radiation in the 4.75–5.05 THz band, with a divergence angle of < 5 ∘ <5^° along the plane of the QCLs substrate. Abstract : The internal structure of a THz QCL waveguide module.